The Analysis Study of Surgical Management of Intussusception : A Pediatric Surgery Systematic Review - Yosie Yulanda Putra; Ririn Azhari (The International Journal of Medical Science and Health Research, 2024)
Background: Intussusception, a common abdominal emergency in children under three years of age, can lead to serious complications due to abnormal bowel movements, anatomical abnormalities, and infection. Surgical management is required if non-surgical reduction fails. Methods: This systematic review adheres to the PRISMA 2020 principles, focusing on full-text papers published in English between 2014 and 2024. Editorial and review articles without DOIs were removed to ensure that only high-quality sources were included. A comprehensive literature search was performed using major databases such as ScienceDirect, PubMed, and SagePub to uncover studies related to this research issue. Results: The database search identified over 1000 relevant publications, and eight were selected for in-depth analysis. Each study underwent rigorous critical appraisal to ensure quality and relevance, which formed the basis for a comprehensive review of the role of surgical management in the management of pediatric intussusception. Conclusions: Intussusception is a common condition in children under three years of age, with 85% of cases occurring during infancy. Surgical management is critical to the clinical outcome, with ultrasonography being the preferred diagnostic method. Secondary intussusception occurs in 1.5 to 15% of cases. In developing countries, surgical management is more common due to late diagnosis and limited access to radiological reduction methods.